Women Religious and Epistolary Exchange in the Carmelite Reform: The Disciples of Teresa de Avila - García Romero, María del Castillo (Trocadero. Revista del Departamento de Historia Moderna, Contemporánea, de América y del Arte, 2020)
Reseña de obra: Women Religious and Epistolary Exchange in the Carmelite Reform. The Disciples of Teresa de Ávila (Ámsterdam, 2020, Amsterdam University Press, 327 páginas. ISBN: 978-94-6372-343-5)